Antidiabetic Activity of Ruellia tuberosa L., Role of α-Amylase Inhibitor: In Silico, In Vitro, and In Vivo Approaches. (21st October 2015) - Ratna Wulan, Dyah; Priyo Utomo, Edi; Mahdi, Chanif
Abstract : Ruellia tuberosa L. is a folk remedy in the treatment of diabetes mellitus. However, its hypoglycemic activity has not been investigated so far. In the present study, the antidiabetic mechanism of the n-hexane fraction of methanolic extract (HFME) of this plant was investigated in silico, in vitro, and in vivo . In silico study was performed using AutoDock4.2 software. In vitro    α -amylase inhibitory activity was investigated by starch-iodine method. A single dose of 450 mg/kg HFME for 14 days was subjected to an antidiabetic screening in vivo by a multiple low dose streptozotocin (MLD-STZ) induced rats. Molecular modeling results show that Betulin exhibited noncompetitive α -amylase inhibitory activities. The effect of HFME elicited significant reductions of diabetic rat blood glucose. A single dose administration of HFME inhibited α -amylase activity in vivo (P < 0.01 ) compared to a diabetic control group. Moreover, this extract strongly inhibited the α -amylase activity in vitro (IC50 0.14 ± 0.005 mg/mL). It is concluded that HFME exerted an antidiabetic effect via α -amylase inhibitor. Our findings provide a possible hypoglycemic action of R. tuberosa L. as an alternative therapy in the management of diabetes.